Komparasi Metode Weighted Aggregated Sum Product Assessment (WASPAS) dan Multi-Objective Optimization on The Basis of Ratio (MOORA) Dalam Penerimaan Dosen - Novi Lestari; Joni Karman; Budi Santoso (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The acceptance of Lecturers in a University should be through the stage seleski. In the selection process will be produced a decision. To obtain a good decision then required a system supporting the decision, known as SPK. DSS is an information system interactive that provides information specifically aims to solve a particular problem, whether the problem is structured or unstructured. There are many methods that can help in the system of supporting decision. In research this will be done a comparison or the comparison of the method of Weighted Aggregated Sum Product Assessment (WASPAS) and the method of Multi-Objective Optimization On The Basis Of Ratio (MOORA). The purpose of this research is to view a comparison of the magnitude of the final value of the two methods in selecting Lecturer Candidates will be accepted. The second method used by some of the criteria of judging that have been defined. On the method of WASPAS results highest with the total value of the end is 1.30663 automatically gets a rank of one, while in the method of MOORA results the highest value is 0.46504 be at rank one. From the second the end result of this method can be seen that among the methods of WASPAS and methods of MOORA have different results